Green banking - Drobnjaković, Maja (Journal of Economic Development, Environment and People, 2013)
There is an urgent need to march towards “low - carbon economy”. Global challenges of diminishing fossil fuel reserves, climate change, environmental management and finite natural resources serving an expanding world population - these reasons mean that urgent action is required to transition to solutions which minimize environmental impact and are sustainable. We are at the start of the low - carbon revolution and those that have started on their low - carbon journey already are seeing benefits such as new markets and customers, improved economic, social and environmental performance, and reduced bills and risks. Green investment banks offer alternative financial services: green car loans, energy efficiency mortgages, alternative energy venture capital, eco - savings deposits and green credit cards. These items represent innovative financial products.